1999
DOI: 10.1111/j.1752-1688.1999.tb04237.x
|View full text |Cite
|
Sign up to set email alerts
|

POTENTIAL EFFECTS OF CLIMATE CHANGE ON AGRICULTURAL WATER USE IN THE SOUTHEAST U.S.1

Abstract: Climate change has the potential to have dramatic effects on the agricultural sector nationally and internationally as documented in many research papers. This paper reports on research that was focused on a specific crop growing area to demonstrate how farm managers might respond to climate‐induced yield changes and the implications of these responses for agricultural water use. The Hadley model was used to generate climate scenarios for important agricultural areas of Georgia in 2030 and 2090. Linked crop re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…Water use per-capita has steadily declined in the United States since the mid-1980s as a result of new technologies that require less water, improved industrial efficiency, increased water recycling, and changes in water regulations (Solley and Perlman, 1999). Genetic engineering of crops is expected to reduce water requirements for some agricultural products (Hatch et al, 1999). Thermoelectric power generation has also not increased since the 1980s, despite warmer air temperatures.…”
Section: Simulations Of Hydrologic Conditions In the Southmentioning
confidence: 99%
“…Water use per-capita has steadily declined in the United States since the mid-1980s as a result of new technologies that require less water, improved industrial efficiency, increased water recycling, and changes in water regulations (Solley and Perlman, 1999). Genetic engineering of crops is expected to reduce water requirements for some agricultural products (Hatch et al, 1999). Thermoelectric power generation has also not increased since the 1980s, despite warmer air temperatures.…”
Section: Simulations Of Hydrologic Conditions In the Southmentioning
confidence: 99%
“…However, we did not consider the direct effects of increased CO 2 concentrations on the joint physiological and structural effect on plant growth and related water savings during the growing period of crops. Thus, several studies which considered potential shortening of the growing seasons due to increase in growing season temperature and CO 2 fertilization reported a decrease or only modest increase in irrigation water requirements for these crops in different regions of the United States [26,27]. Konzmann et al [28] stated that increases of >20% are projected with a low likelihood, for parts of Asia and North America; they further argued that if CO 2 effects were ignored, however, global irrigation demand would remain constant, and increases would prevail globally except for Southern Asia where higher precipitation is projected.…”
Section: Crop Irrigation Requirement Uncertainties Between General CImentioning
confidence: 99%
“…The cropping systems and physical characteristics of the Lowndes county area are similar to those in other agricultural growing areas of the southern coastal plain and piedmont. Hatch et al (1999) used simulation modeling in the agricultural growing of the coastal plain of Georgia to show the likely impacts of climate-induced yield changes. The linked climatecrop response-farm management modeling effort indicated that the beneficial aspects of the HADCM2 climate scenario could be expected to increase double cropping, decrease fallowing of crop land, decrease water use per acre, but expand irrigation capacity and increase income.…”
Section: Water Resources Implicationsmentioning
confidence: 99%